Review Paper on Data Mining Techniques and Applications (International Journal of Innovative Research in Computer Science & Technology, 2019)
Data mining is the process of extracting  hidden and useful patterns and information from data. Data mining is a new technology that helps businesses to  predict future trends and behaviors, allowing them to  make proactive, knowledge driven decisions. The aim of  this paper is to show the process of data mining and how  it can help decision makers to make better decisions.  Practically, data mining is really useful for any  organization which has huge amount of data. Data  mining help regular databases to perform faster. They  also help to increase the profit, because of the correct  decisions made with the help of data mining. This  paper shows the various steps performed during the
Keywords: Data Mining; regression; Time series; prediction; association